Schiff Base-Benzil of Iron (III), Cerium (IV) and Thorium (IV) Mixed Ligand Chelates: Preparation, Spectral Characterization, Antitumor Activity and Molecular Docking Studies - Al-Fakhry , Bahia; Elamin, Saadelin; Bufarwa, Saleh; Belaidi, Mustapha; El-ajaily, Marei (AlQalam Journal of Medical and Applied Sciences, 2025)
In the following study, Schiff base formed from the condensation of 2-hydroxyacetophenone and L-alanine as the main ligand (HL1) and benzil compound as secondary ligand were entered into the formation of three new combined ligand chelates of Fe(III), Ce(IV), and Th(IV) ions. The fashioned chelates were characterized through using numerous analytical and spectroscopic equipment. The analytical techniques showed a non-electrolytic nature character for all chelates; moreover, the CHNS elemental analyses exhibited the formation of the mixed ligand chelates in a 1:1:1 [ML1L2] ratio. Meanwhile, the infrared spectral information showed the bonding of the metal ions with the active organizations present within the free ligands (-C=N, NH2, -OH). Also, the electronic spectral results displayed the proper geometrical structures for the mixed ligand chelates. In vitro antitumor activity of a few synthesized compounds with human Hepatocellular Carcinoma cells (Hep-G2) was tested. Additionally, the molecular docking ligand interactions have been evaluated.